Penerapan Model Pembelajaran Children Learning in Science untuk Meningkatkan Hasil Belajar Siswa Kelas V - Muslimin Muslimin; Lukman Lukman; Sri Fadila (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the improvement of student learning processes and outcomes through the application of the Children Learning In Science (CLIS) learning model on the water cycle of class V UPT SD Negeri 2 Gandangbatu Sillanan, Tana Toraja Regency. This research approach uses a qualitative approach and the type of research used is Classroom Action Research (PTK). The subjects in this study were fifth grade students of UPT SD Negeri 2 Gandangbatu Sillanan in the 2022/2023 school year, totaling 23 students consisting of 11 boys and 12 girls, and a teacher. Data analysis techniques used are data condensation, data presentation and conclusion drawing which are processed qualitatively. Based on the data obtained during the implementation of cycles I and II, the research results for cycle I were in the Fair category (C) and for cycle II were in the category (B). The conclusion of this study is that the process and learning outcomes of students about the water cycle of class V UPT SD Negeri 2 Gandangbatu Sillanan, Tana Toraja Regency by applying the Children Learning In Science learning model has increased.